System usability, stress and mood among teachers using distance learning - Maria Grazia MAGGIO; Amelia RIZZO; Maria Chiara STAGNITTI; Alfredo MANULI; Rocco Salvatore CALABRO (GIornale Italiano di Psicologia e Medicina del Lavoro, 2022)
Introduction: Literature on teachers’ stress and depression over the past two years is vast, conversely, evidence regarding relationships between system usability and mood is relatively small. The present cross-sectional study aimed to explore system usability, stress, and mood among teachers using distance learning (DL). Methods: A digital protocol containing socio-demographic data, the Depression Anxiety Stress Scales (DASS-21), the System Usability Scale (SUS), and three qualitative questions on DL was administered to 106 Italian teachers (89.4% of women; spanning from 27 to 67 years old; mean age in years 47.10 ± 10.23). Results: Linear regression showed that there were no statistically significant effects of age, gender, and school grade. Stress was significantly correlated with anxiety and depressive symptoms, while DL usability was negatively correlated with stress, anxiety, and depression. Discussion and Conclusions: Teachers showed high acceptance of the DL. However, it was characterised in predominantly mild but negative terms. Our findings highlight the psychological impact of the massive DL on teachers’ mood and stress levels, as well as differences in perceived ease of use of the system, suggesting the need for tailored and blended didactic strategies.